Small town rules : how big brands and small businesses can prosper in a connected economy - Moltz, Barry J. (Que, 2012)
Technology and economics are transforming business in a completely unexpected way: suddenly, even the largest companies must compete as if they were small, local businesses. Suddenly, your customers can talk to everyone else across the nation, and people listen to them, not your carefully crafted advertising or branding. It's just like doing business in a small town, where "reputation is forever." Suddenly, communities and personal connections are critical to your success - just as they've always been in small towns. The best small-town and rural entrepreneurs have been successfully overcoming these challenges for centuries. Their lessons and techniques are suddenly intensely valuable to even the largest companies, most dominant brands, and most cosmopolitan businesses. Small Town Rules adapts these lessons and techniques for today's new "global small town": one knitted together through the Web, Facebook, and Twitter. Two pioneering entrepreneurs and social media experts show how to: * Survive seasonal cycles and year-to-year fluctuations the way rural farmers and businesses do * Use "small town entrepreneur secrets" for coping with limited access to people and capital * Reduce risk by "piecing together" multiple income sources * Start using customer-driven communication to your advantage * Interact with customers on a more human scale, no matter how big you are * Rediscover your company's local roots, and more.